Optimal. Leaf size=29 \[ e^{\log ^2(x)}-x+\frac {4 e^{-2 e^{-x+x^2}}}{\log ^2(16)} \]
________________________________________________________________________________________
Rubi [F] time = 1.26, antiderivative size = 0, normalized size of antiderivative = 0.00, number of steps used = 0, number of rules used = 0, integrand size = 0, \(\frac {\text {number of rules}}{\text {integrand size}}\) = 0.000, Rules used = {} \begin {gather*} \int \frac {e^{-2 e^{-x+x^2}} \left (e^{-x+x^2} \left (8 x-16 x^2\right )-e^{2 e^{-x+x^2}} x \log ^2(16)+2 e^{2 e^{-x+x^2}+\log ^2(x)} \log ^2(16) \log (x)\right )}{x \log ^2(16)} \, dx \end {gather*}
Verification is not applicable to the result.
[In]
[Out]
Rubi steps
\begin {gather*} \begin {aligned} \text {integral} &=\frac {\int \frac {e^{-2 e^{-x+x^2}} \left (e^{-x+x^2} \left (8 x-16 x^2\right )-e^{2 e^{-x+x^2}} x \log ^2(16)+2 e^{2 e^{-x+x^2}+\log ^2(x)} \log ^2(16) \log (x)\right )}{x} \, dx}{\log ^2(16)}\\ &=\frac {\int \left (e^{-2 e^{(-1+x) x}+(-1+x) x} (8-16 x)-\log ^2(16)+\frac {2 e^{\log ^2(x)} \log ^2(16) \log (x)}{x}\right ) \, dx}{\log ^2(16)}\\ &=-x+2 \int \frac {e^{\log ^2(x)} \log (x)}{x} \, dx+\frac {\int e^{-2 e^{(-1+x) x}+(-1+x) x} (8-16 x) \, dx}{\log ^2(16)}\\ &=-x+2 \operatorname {Subst}\left (\int e^{x^2} x \, dx,x,\log (x)\right )+\frac {\int \left (8 e^{-2 e^{(-1+x) x}+(-1+x) x}-16 e^{-2 e^{(-1+x) x}+(-1+x) x} x\right ) \, dx}{\log ^2(16)}\\ &=e^{\log ^2(x)}-x+\frac {8 \int e^{-2 e^{(-1+x) x}+(-1+x) x} \, dx}{\log ^2(16)}-\frac {16 \int e^{-2 e^{(-1+x) x}+(-1+x) x} x \, dx}{\log ^2(16)}\\ \end {aligned} \end {gather*}
________________________________________________________________________________________
Mathematica [A] time = 0.30, size = 29, normalized size = 1.00 \begin {gather*} e^{\log ^2(x)}-x+\frac {4 e^{-2 e^{-x+x^2}}}{\log ^2(16)} \end {gather*}
Antiderivative was successfully verified.
[In]
[Out]
________________________________________________________________________________________
fricas [B] time = 0.80, size = 59, normalized size = 2.03 \begin {gather*} -\frac {{\left (4 \, x e^{\left (2 \, e^{\left (x^{2} - x\right )}\right )} \log \relax (2)^{2} - 4 \, e^{\left (\log \relax (x)^{2} + 2 \, e^{\left (x^{2} - x\right )}\right )} \log \relax (2)^{2} - 1\right )} e^{\left (-2 \, e^{\left (x^{2} - x\right )}\right )}}{4 \, \log \relax (2)^{2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
giac [B] time = 0.21, size = 68, normalized size = 2.34 \begin {gather*} -\frac {{\left (4 \, x e^{\left (x^{2} - x\right )} \log \relax (2)^{2} - 4 \, e^{\left (x^{2} + \log \relax (x)^{2} - x\right )} \log \relax (2)^{2} - e^{\left (x^{2} - x - 2 \, e^{\left (x^{2} - x\right )}\right )}\right )} e^{\left (-x^{2} + x\right )}}{4 \, \log \relax (2)^{2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maple [A] time = 0.06, size = 25, normalized size = 0.86
method | result | size |
risch | \({\mathrm e}^{\ln \relax (x )^{2}}+\frac {{\mathrm e}^{-2 \,{\mathrm e}^{x \left (x -1\right )}}}{4 \ln \relax (2)^{2}}-x\) | \(25\) |
default | \(\frac {4 \,{\mathrm e}^{-2 \,{\mathrm e}^{x^{2}-x}}-16 x \ln \relax (2)^{2}+16 \ln \relax (2)^{2} {\mathrm e}^{\ln \relax (x )^{2}}}{16 \ln \relax (2)^{2}}\) | \(39\) |
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
maxima [A] time = 0.60, size = 51, normalized size = 1.76 \begin {gather*} -\frac {4 \, x \log \relax (2)^{2} - {\left (4 \, e^{\left (\log \relax (x)^{2} + 2 \, e^{\left (x^{2} - x\right )}\right )} \log \relax (2)^{2} + 1\right )} e^{\left (-2 \, e^{\left (x^{2} - x\right )}\right )}}{4 \, \log \relax (2)^{2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
mupad [B] time = 3.44, size = 26, normalized size = 0.90 \begin {gather*} {\mathrm {e}}^{{\ln \relax (x)}^2}-x+\frac {{\mathrm {e}}^{-2\,{\mathrm {e}}^{-x}\,{\mathrm {e}}^{x^2}}}{4\,{\ln \relax (2)}^2} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________
sympy [A] time = 0.92, size = 26, normalized size = 0.90 \begin {gather*} - x + e^{\log {\relax (x )}^{2}} + \frac {e^{- 2 e^{x^{2} - x}}}{4 \log {\relax (2 )}^{2}} \end {gather*}
Verification of antiderivative is not currently implemented for this CAS.
[In]
[Out]
________________________________________________________________________________________